2012
DOI: 10.1097/scs.0b013e31825e4ad6
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic Study in Patients With Surgically Treated Facial Fractures

Abstract: This study, using surface electromyography, analyzed the activity of the masseter muscles of 30 patients with facial bone fractures that were surgically treated. Evaluations were made before surgery and in the 7th, 30th, and 60th days after surgery. The value of each measure and the average of 3 maximum voluntary isometric contractions lasting 5 seconds each were registered, and statistical analyses were performed. Patients had a mean age of 31 years and an average of 1.33 fractures. They were grouped accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
7

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
2
5
0
7
Order By: Relevance
“…This is consistent with the results of the study of Campolongo et al [5] but they studied masseter activity only and detected a marked drop at 7 days postoperatively.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is consistent with the results of the study of Campolongo et al [5] but they studied masseter activity only and detected a marked drop at 7 days postoperatively.…”
Section: Discussionsupporting
confidence: 92%
“…All patients showed recovery of muscular activity in 6 weeks, near the value of the study of Campolongo et al (60 days) [5] but still significantly lower than the values of normal sides.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…Such cases represented 6.6 % of all facial fractures. Other studies have shown a higher frequency of these fractures in maxillofacial trauma, ranging from 10 to 18.2 % [9, [13][14][15]. However, these figures include maxillary dentoalveolar trauma, The total of approaches surpasses the number of patients surgically treated, as many presented with associated facial fractures which represents a significant proportion of cases [9,16].…”
Section: Discussionmentioning
confidence: 98%